2008
DOI: 10.1103/physreve.78.056108
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying local structure effects in network dynamics

Abstract: Mutual information between the time series of two dynamical elements measures how well their activities are coordinated. In a network of interacting elements, the average mutual information over all pairs of elements I is a global measure of the correlation between the elements' dynamics. Local topological features in the network have been shown to affect I . Here we define a generalized clustering coefficient C_{p} and show that this quantity captures the effects of local structures on the global dynamics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(84 citation statements)
references
References 18 publications
5
79
0
Order By: Relevance
“…As an extension of the ground state quantum phase transition (QPT) [1,2], an excited-state quantum phase transition (ESQPT) is identified as the singular behaviors of the excited state as the control parameter passes through the critical point [3][4][5][6]. A remark feature of ESQPTs is the divergence of the density of states at higher excitation energies [5][6][7][8]. In the last two decades, ESQPTs have been studied in various models, both theoretically (see, e.g., Ref.…”
mentioning
confidence: 99%
“…As an extension of the ground state quantum phase transition (QPT) [1,2], an excited-state quantum phase transition (ESQPT) is identified as the singular behaviors of the excited state as the control parameter passes through the critical point [3][4][5][6]. A remark feature of ESQPTs is the divergence of the density of states at higher excitation energies [5][6][7][8]. In the last two decades, ESQPTs have been studied in various models, both theoretically (see, e.g., Ref.…”
mentioning
confidence: 99%
“…Previous studies shown that increasing C p tends to strongly enhance I [21], thus explaining why S. cerevisiae core network exhibits much higher values of I than the Rand-Beta model.…”
Section: Resultsmentioning
confidence: 96%
“…This is known to enhance the ability of networks to propagate information [21]. However, another interpretation is possible for the high C p .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hilbert space H s as a whole can be seen as a stratified manifold foliated by the SU (2) orbits of all the possible configurations of constellations [16]. In addition, the Majorana constellation has been useful in other applications, such as the classification of spinor Bose-Einstein-condensate phases [17][18][19] or the investigation of the thermodynamical limit in the Lipkin-Meshkov-Glick model [20,21]. This representation also plays a role in the Atiyah mapping related to his conjecture on 'configurations of points' [22].…”
Section: Introductionmentioning
confidence: 99%